AUDITAJE A PROCESOS DE RECOLECCION, VALIDACIÓN Y MINERÍA DE DATOS SOCIALES. - Compilación, Ceo (La Sociología en sus Escenarios, 2012)
Abstract. In the applied social research a series of technical processes is developed to provide the researchers with the necessary materials, as well as to its organization so that the activities and/or services can be developed or be rendered of an advisable way and be obtained the awaited results. These technical processes must constantly be evaluated by means of audit processes. WHAT IS AN AUDIT? It is a systematic process (planned and programmed activity), independent (the auditor must be independent of the audited area.), participating and documented, to obtain evidence and to evaluate it objectively, with the purpose of to determine in what degree the criteria of the audit are fulfilled. Auditor (or contralor) to the enabled and experienced person that is designated by a competent authority, to review, to examine and to evaluate the results of the administrative and financial management of a dependency or organization in order of informing or of considering about them, realising the pertinent observations and recommendations to improve its effectiveness and efficiency in its performance. Resumen. En los procesos de investigación social aplicados se desarrollan una serie de procesos técnicos tendientes a proveer a la organización de los materiales necesarios, así como a su adecuada organización para que las actividades y/o servicios se puedan desarrollar o prestar de una manera conveniente y lograr los resultados esperados. Estos procesos técnicos deben ser constantemente evaluados mediante procesos de auditoría. ¿QUÉ ES UNA AUDITORIA? Es un proceso sistemático (actividad planificada y programada), independiente (el auditor deben ser independientes del área auditada.), participativo y documentado, para obtener evidencia y evaluarla objetivamente, con el fin de determinar en qué grado se cumplen los criterios de la auditoria.